Case Report: Extramedullary plasmacytoma of the stomach: a rare manifestation of relapsed multiple myeloma - Dirican, Canan D.; Ajayi, Folasade; Al Mardini, Anas; Bijoy, Sneha; Shaaban, Hamid; Guron, Gunwant (Frontiers in Hematology, 2025)
BackgroundExtramedullary plasmacytoma (EMP) involving the gastrointestinal (GI) tract is a rare and serious manifestation of multiple myeloma (MM), often indicative of disease relapse and poor prognosis.Case presentationWe report a case of a 64-year-old female with MM previously treated with cyclophosphamide, bortezomib, and dexamethasone (CyBorD) chemotherapy, autologous stem cell transplant, and denosumab, who presented four months post-transplant with melena. Esophagogastroduodenoscopy revealed a submucosal gastric nodule. Histopathology and flow cytometry confirmed monoclonal IgG kappa plasma cell infiltration, consistent with plasmacytoma. Bone marrow biopsy demonstrated remission with less than 3% plasma cells. The patient received local radiotherapy and was started on a daratumumab-based chemotherapy regimen for relapsed MM.ConclusionSecondary EMP involving the stomach is an exceedingly rare but important differential in MM patients presenting with GI bleeding. This case highlights the need for vigilance in monitoring for extramedullary relapse post-transplant, as early diagnosis and aggressive treatment may impact outcomes.